Jordanian National Study of Nurses’ Barriers and Predictors for Research Utilization in Clinical Settings - Abuhammad S; Alzoubi K; Khabour O; Mukattash T (Dove Medical Press, 2020)
Sawsan Abuhammad,1 Karem Alzoubi,2 Omar Khabour,3 Tareq Mukattash2 1Department of Maternal and Child Health, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Clinical Pharmacy, Jordan University of Science and Technology, Irbid 22110, Jordan; 3Department of Medical Laboratory Sciences, Jordan University of Science and Technology, Irbid 22110, JordanCorrespondence: Sawsan Abuhammad Email Shabuhammad@just.edu.joBackground: The nurses are the healthcare providers and researchers in the health institutions. Investment in the research potential of nurses will ultimately benefit society. The purpose of this study was to survey nurses regarding barriers to participating in research studies.Methods: This was a cross-sectional descriptive study using electronic surveys sent by email, and social media groups (WhatsApp). A total of 447 nurses agreed to participate in this study. Barriers were measured using the Barriers of Research Utilization (BRU) Scale.Results: More than half (53.3%) of the participants perceived the barriers to be high, whereas a small fraction (8.9%) perceived them as low. Barriers related to the organization scored the highest (P< 0.01) compared to the other domains (nurse, innovation, and communication). The regression analysis model showed that age, working experience, and nationality were associated with barriers to participate in research (P< 0.05).Conclusion: More than half of the nurses in Jordan perceived barriers to participating in research studies to be high. The barriers associated with the organization had more influence. A comprehensive approach should be developed to boost research utilization among nurses by overcoming the barriers identified in the current study.Keywords: barriers, nurses, research, clinical settings, research utilization